Digital Hegemony: Influencer Marketing in the Reproduction Process of the Dominant Ideology - Meriç Kılınç; Başak Nur Gökçam (4. Boyut Medya ve Kültürel Çalışmalar Dergisi)
This research examines the role of neoliberal ideology in media and cultural production processes. The primary aim is to determine how and to what extent values associated with neoliberalism—such as consumption, fashion, hedonism, individuality, competition and success, property and wealth, freedom, travel, beauty, entertainment, innovation, and technology—are represented in the influencers’ social media content. Given the significant influence of social media platforms on broad audiences, understanding this content’s impact on societal norms and values is crucial from cultural and social dynamics perspectives. The study employs qualitative content analysis, focusing on the Instagram posts of the 10 most popular influencers in Turkey. A total of 267 posts were coded, and the findings were evaluated using frequency and percentage calculations. The findings reveal that influencer content significantly promotes neoliberal values, including consumer culture, fashion and beauty standards, and the ideals of travel and freedom, beyond merely promoting products and services. This study is expected to highlight the role of influencer marketing in the reproduction of neoliberal values. This research contributes to the literature on media and cultural studies by providing a framework for understanding the impact of social media content on individuals and collective memory.